Hubungan Karateristik Maloklusi Gigi Anterior Terhadap Kondisi Psikososial Remaja : (Kajian pada Remaja SMAN 1 Sambas Berdasarkan MIQ) - Febryanti, Feby; Nofrizal, Riko (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Background: Malocclusion is one of the dental health problems that can have an impact on the psychosocial condition of adolescents. The most common charateristics of anterior dental malocclusion are crowding, diastema and protrusion. Anterior dental malocclusion has impact on quality of life. To see the impact of malocclusion on young people, a questionnaire called the MIQ (Malocclusion Impact Questionnaire) can be used. Objective: The aim of this study is to explore the relationship between charateristics of anterior dental malocclusion with psychosocial conditions of adolescents in SMAN 1 Sambas based on MIQ. Method: This was an analytical observational study with cross sectional design. The research sample was selected using a simple random sampling technique, namely the technique of taking samples from the population in a random way without regard to certain strata. Anterior dental malocclusion examination through a zoom application by an orthodontist specialist dentist and measurement of psychosocial conditions using a MIQ questionnaire which is divided into a google form. Data presentation is done in the form of frequency distribution table. Result: The contingency coefficient correlation test showed that there was no significant relationship between the charateristics of anterior dental malocclusion with psychosocial conditions of adolescents at SMAN 1 Sambas p>0,05 (p=0,987) with a weak relationship strength with a positive correlation that was not clinically significant. Conclusion: This study showed no significant correlation between charateristics of anterior dental malocclusion with psychosocial conditions of adolescents